Physico-chemical and biological behaviour of eggshell bio-waste derived nano-hydroxyapatite matured at different aging time. (June 2021) - Das Lala, Sumit; Barua, Emon; Deb, Payel; Deoghare, Ashish B.
Graphical abstract: Highlights: Conversion of waste chicken eggshells into nano-hydroxyapatite. Phosphate precursor Na2 HPO4 renders proper crystallization of the synthesized HAp. Aging time of 12 h (HAp12) provides the best optimized physico-chemical properties. HAp 12 sample shows bioactive, biodegradable and non-cytotoxic properties. HAp 12 sample also shows maximum BSA protein adsorption. Abstract: The present study explores the effect of aging time on the properties of nano-hydroxyapatite (HAp) synthesized from chicken eggshells. CaO obtained from eggshells serves as calcium precursor which is combined with di-sodium hydrogen phosphate (Na2 HPO4 ) as a phosphate precursor for the synthesis of HAp. The reaction precipitate is allowed to mature considering aging times of 12, 24, 36 and 48 h. The synthesized powders are characterized using FTIR and XRD to confirm the HAp formation. SEM micrographs of all the aged samples reveal dense agglomerated HAp particles. It is observed from the TEM results that the particle morphology of all the HAp samples appears to be nano-sized, spherical-shaped and polycrystalline in nature. A novel relationship between relative density vs. aging time is also established where relative density is found to increase with an increase in the aging time. In- vitro bioactivity and biodegradability evaluation of 12 h aged HAp with best physico-chemical properties show the formation of HCA apatite layer and significant weight loss respectively. In-vitro cytotoxicity test with Human Wharton's Jelly Mesenchymal Stem Cells (hMSCs) (HiMedia CL001-T25) shows approximately 90 % cell viability assuring non-cytotoxicity of the 12 h aged HAp. The derived HAp can be a possible regenerative biomaterial for bone tissue engineering applications.